Why Most Sugar Pills Are Not Placebos. Issue 5 (December 2015) - Holman, Bennett
Abstract : The standard philosophical definition of placebos offered by Grünbaum is incompatible with Cartwright's conception of randomized clinical trials. I offer a modified account of placebos that respects this role and clarifies why many current medical trials fail to warrant the conclusions they are typically seen as yielding. I then consider recent changes to guidelines for reporting medical trials and show that pessimism over parsing out the cause of "unblinding" is premature. Specifically, using a trial of antidepressants, I show how more sophisticated statistical analyses can parse out the source of such effects and serve as an alternative to placebo control.